(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
We study an unpublished votive inscription found in Oleiros (Silleda, Pontevedra), which is exposed in Pontevedra Museum. Although the monument is damaged, it can be interpreted as a votive offering to the Lusitanian-Gallaecian god Cosus,with an appellative that is unknown up to now. Besides, this inscription confirms that the main area where this god was worshipped was the territory inhabited by the celts of northwestern Hispania.